2006
DOI: 10.1111/j.1745-7254.2006.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol and methylprednisolone on biochemical, neurobehavioral and histopathological recovery after experimental spinal cord injury

Abstract: Aim: To investigate the neuroprotective effect of resveratrol in an experimental spinal cord injury (SCI) model in rats. Methods: Male Wistar albino rats weighing 200-250 g were randomized into six groups. Weight-drop trauma was performed for SCI. Group 1 underwent laminectomy alone. Group 2 underwent laminectomy followed by SCI. Groups 3, 4, 5, and 6 underwent laminectomy followed by SCI and received resveratrol (100 mg/kg), methylprednisolone (MP) (30 mg/kg), resveratrol (100 mg/kg) plus MP (30 mg/kg), and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 64 publications
6
52
0
1
Order By: Relevance
“…MDA is an important and the most commonly used indicator of lipid peroxidation and its level increases in tissues when they are exposed to oxidative stress. Numerous studies have postulated that MDA is significantly increased in animals exposed to traumatic SCI [3,4,8]. The results presented in this study have also indicated that lipid peroxidation increases in all blood, CSF, spinal cord tissues of the rabbits.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…MDA is an important and the most commonly used indicator of lipid peroxidation and its level increases in tissues when they are exposed to oxidative stress. Numerous studies have postulated that MDA is significantly increased in animals exposed to traumatic SCI [3,4,8]. The results presented in this study have also indicated that lipid peroxidation increases in all blood, CSF, spinal cord tissues of the rabbits.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, prevention of lipid peroxidation is important for attenuation of secondary damage. Some neuroprotective agents with antioxidant activity have been investigated in traumatic SCI and some of them have been found useful [3,22]. Due to neuroprotective [10,23] property, we used the dexmedetomidine in SCI and found that it only and slightly reduced lipid peroxidation in CSF and spinal cord tissue of the rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] It was determined that PON-1 and AE activity were significantly lower in patients with multiple traumas ,and those parameters may be beneficial when severity of trauma and potential efficiency of treatment are examined. In the current study, significantly higher serum and tissue TAS and PON-1 activity levels found in post-SCI resveratrol group relative to SCI and post-SCI DMSO groups are consistent with findings of Ates et al (2006;2007) indicating increased glutathione peroxidase level in rats given resveratrol after SCI and head trauma. [13,25] Elmali et al demonstrated that resveratrol significantly reduced MDA level in ischemia/reperfusion damage of skeletal muscle.…”
Section: (A) (B) (C)supporting
confidence: 79%
“…[13,25] Elmali et al demonstrated that resveratrol significantly reduced MDA level in ischemia/reperfusion damage of skeletal muscle. [26] It was also observed in the current study that TAS level, which indicates total antioxidative effect, increased in resveratrol treatment group. It can be speculated that effect derives from anti-oxidative effect and free radical scavenging property of resveratrol as determined in the literature, particularly studies conducted by Ates et al (2006;2007).…”
Section: (A) (B) (C)supporting
confidence: 52%